The Kenny music performance anxiety inventory (K-MPAI): Scale construction, cross-cultural validation, theoretical underpinnings, and diagnostic and therapeutic utility - Kenny, Dianna Theadora (Frontiers in Psychology, 2023)
I commenced my academic exploration of music performance anxiety in a study with opera chorus artists from Opera Australia in 2004. I subsequently postulated a new theory of the aetiology of music performance anxiety and began the development of the Kenny Music Performance Anxiety Inventory (K-MPAI) to assess the hypothesized theoretical constructs underpinning its diverse clinical presentations. I proposed a new definition of music performance anxiety in 2009 and revised the item content of the K-MPAI from 26 to 40 in 2011. Over the ensuing years, many researchers have used the K-MPAI in studies on a wide variety of musicians, including vocalists and instrumentalists, popular and classical musicians, tertiary music students, and professional, solo, orchestral, ensemble, band, and community musicians. To date, the K-MPAI has been reported in more than 400 studies and has been translated into 21 languages. It has been the subject of more than 39 dissertations. In this paper, I examine the research that has used the K-MPAI to ascertain how well the theory, assessment tool, and its cross-cultural validation have provided evidence for its factorial structure, robustness, and utility. The evidence indicates that the factorial structure remains consistent across cultures and different populations of musicians. It has good discriminative ability and utility for diagnostic purposes. I conclude with some reflections on how the K-MPAI can guide therapeutic interventions and with some thoughts on future directions.